2017
DOI: 10.3390/app7030248
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Wet Compression by the Electronic Expansion Valve Opening on the Performance of a Heat Pump System

Abstract: Abstract:In this study, by controlling the Electronic Expansion Valve opening, the influence of wet compression on a heat pump system was experimentally investigated in different heating conditions. The results demonstrate that the discharge temperature decreased and the mass flow rate increased, due to quality of the rising liquid droplets. It was also found that the heating capacity and power input of wet compression increased more than that of dry compression, with a superheat of 10 • C. The maximum COP (Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Liang et al [8] and Hu et al [9] presented the optimum design and a prediction model of heat exchangers. Other studies [10][11][12][13] reported various approaches for improving efficiency and to mitigate GHG emissions. All these studies are indispensable for continuous progress, and guarantee steady steps toward reducing direct and indirect emissions of GHGs.…”
Section: Fundamental Process Components and Mechanical Vapor Comprementioning
confidence: 99%
“…Liang et al [8] and Hu et al [9] presented the optimum design and a prediction model of heat exchangers. Other studies [10][11][12][13] reported various approaches for improving efficiency and to mitigate GHG emissions. All these studies are indispensable for continuous progress, and guarantee steady steps toward reducing direct and indirect emissions of GHGs.…”
Section: Fundamental Process Components and Mechanical Vapor Comprementioning
confidence: 99%
“…Additionally, wet compression can make the vapor compression refrigeration cycle with pure working fluid closer to the ideal Carnot cycle. When the suction dryness is low, the liquid droplets drawn into the compressor completely vaporize within a short time, thereby improving compressor performance and reducing discharge temperature [27]. The wet compression cycle offers the highest possible efficiency for thermodynamic cycles operating between two temperatures with a heat sink and heat source [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…It indicated that the air-conditioner with two-phase suction injection had the maximum mean cooling capacity and was more appropriate in severely high cooling-load seasons. Seong et al 11 tested a heat pump under different suction qualities by controlling the electronic expansion valve and found that the discharge temperature decreased while the mass flow rate increased; the maximum heat capacity and COP occurred at specific quality.…”
Section: Introductionmentioning
confidence: 99%